A comparative analysis of enclitics adverbs in Cebuano and Hiligaynon - Lising, Jenifer Loy V. (Tanglaw: official journal of the College of Education, 2004)
This study analyzes the semantic meanings and syntactic distribution of the Cebuano and Hiligaynon counterparts of 15 Tagalog enclitic adverbs in selected Cebuano short stories and Hiligaynon plays. The enclitic adverbs from the literary sources were then compared with those derived from a translation task administered to native speakers of Cebuano and Hiligaynon, The results shoe that all the Tagalog enclitic adverbs have counterparts in Cebuano and Hiligaynon, except for the politeness markers po and ho. Analysis also revealed that some Cebuaano and Hiligaynon enclitic adverbs can have different meanings and various morphological realizations.